High-performance quantum memory device structure

By adopting the self -spin and heterogeneous knot with a three -layer material structure, data storage is used with anomalous Hall effect, and the existing MRAM structure preparation process is complex and high -power High -performance storage device.

CN119343046APending Publication Date: 2025-01-21UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411348421.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing magnetic random memory (MRAM) structures have problems such as complex preparation process, high power consumption, and high critical current density of magnetic moment flip, making it difficult to achieve high-performance memory devices with low power consumption, high speed and simple preparation process.

Method used

Self -spin and heterogeneous knots with a three -layer material structure, including vesometer (GD3GA5O12, GGG) substrate, BI doped rare earth iron pitch (BI: Hoig) film, and AU doped PTBI alloy (AU: PTBI ) Heavy metal film, prepared through methods such as liquid phase extension and DC magnetic sputtering, and use the abnormal Hall effect to achieve data storage.

Benefits of technology

Realize low -power, high -speed, and simple high -performance MRAM structures, reduce the unit writing current density and read current, improve the storage speed and accuracy, and have non -easy loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343046A_ABST
    Figure CN119343046A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance quantum memory device structure, and belongs to the field of novel magnetic random access memories. According to the invention, a spin heterojunction is constructed and an abnormal Hall effect (AHE) is utilized to change a Hall voltage so as to realize storage of data '0' and '1'. The spin heterojunction is composed of three layers of materials which are respectively a single crystal substrate gadolinium gallium garnet (Gd3Ga5O12, GGG), a Bi-doped rare earth iron garnet film Bi: HoIG and a heavy metal layer Au-doped PtBi alloy Au: PtBi from bottom to top, and the heavy metal layer is of a cross structure. The memory device structure is small in critical flip current, low in power consumption, high in storage speed, simple to prepare, low in manufacturing cost and short in manufacturing period. And the memory device structure has the advantages of non-volatility, good film material quality and excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of novel magnetic random access memory, and in particular relates to a quantum spin memory device MRAM structure based on the anomalous Hall effect (AHE). Background Art

[0002] Memory is one of the important components of computers. With the development of the times, traditional semiconductor storage technology and new storage technology are constantly developing. For traditional memory, most of them rely on the accumulation of charge to realize the storage function, and use the "presence" and "absence" of charge to represent the binary logic "1" and "0", such as static random access memory (SRAM) and dynamic random access memory (DRAM). However, as the size of semiconductor process continues to shrink, the manufacturing process of traditional semiconductor memory becomes more difficult, and as the size of CMOS becomes smaller, the static power consumption of traditional semiconductor memory will also increase exponentially. As the size of electronic devices continues to decrease, the spin quantum effect of electrons gradually increases. In this context, people are eager to seek a new storage technology, so magnetic random access memory (MRAM) came into being.

[0003] MRAM is a new type of memory based on electron spin. The basic storage unit of MRAM memory is the magnetic tunnel junction (MTJ). MTJ can be abstracted as a three-layer structure: free layer, oxide layer, and fixed layer. The magnetic tunnel junction (MTJ) stores data through the change of magnetic moment. When the magnetic moments of the free layer and the fixed layer are parallel, it presents a low resistance state. When the magnetic moments of the free layer and the fixed layer are anti-parallel, it presents a high resistance state. The high resistance state corresponds to binary logic "1", and the low resistance state corresponds to binary logic "0". The magnetic moment is induced to reverse through electric current to achieve data writing. MRAM has both the speed of SRAM and the high integration of DRAM, and can be used in cache, storage and computing chips.

[0004] However, in reality, the process of preparing a magnetic tunnel junction (MTJ) is extremely complicated, requiring multiple operations such as photolithography and ion beam etching. The critical current density of the MTJ magnetic moment reversal is also relatively large, and the power consumption is relatively high.

[0005] Therefore, it is very necessary to propose a new type of MRAM device structure. The technical problem that needs to be solved is to design a high-performance quantum memory device MRAM structure with low power consumption, high speed and simple preparation process. Summary of the invention

[0006] Since the MRAM structure in the background technology still has various disadvantages, the present invention proposes a high-performance quantum memory device structure. The structure is a spin heterojunction, which is composed of only three layers of thin film materials and has a very simple preparation process. The first layer substrate is a single crystal substrate gadolinium gallium garnet (Gd 3 Ga5 O 12 , GGG) substrate. Further, the second film is Bi-doped rare earth iron garnet Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) film with a thickness of 30-150nm. Further, the third film is an Au-doped PtBi alloy Au:PtBi heavy metal film with a thickness of 10-15nm. Further, the third heavy metal layer Au:PtBi adopts a cross-shaped structure.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] The present invention first selects gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG) substrate is used as the substrate. Further, in the gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG) substrate by liquid phase epitaxy to grow Bi-doped rare earth iron garnet Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) film. Furthermore, in Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) film by direct current magnetron sputtering to prepare a 10-15 nm thick Au-doped PtBi alloy Au:PtBi heavy metal film. Further, the Au:PtBi heavy metal film is etched into a cross-shaped structure by photolithography to detect the Hall voltage.

[0009] Furthermore, when an in-plane current is passed around the device and the current density is greater than the critical reversal current density of the material's magnetic moment, the SOT (spin-orbit moment) effect is used to induce the material's magnetic moment to flip, and "1" is written when the magnetic moment is vertically upward, and "0" is written when it is vertically downward.

[0010] Furthermore, when a very small detection current is passed through the two ends of the cross-shaped structure of the Au:PtBi heavy metal film, the positive and negative Hall voltages can be detected at the other two ends of the cross-shaped structure. When the Hall voltage is positive, the corresponding storage data is "1", and when the Hall voltage is negative, the corresponding data is "0".

[0011] Furthermore, the writing of binary data "1" and "0" is achieved through the above-mentioned method, and the reading of data is achieved through the cross-shaped thin film structure.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] 1. The high-performance quantum memory device structure proposed by the present invention is composed of only three layers of materials. By constructing a spin heterojunction, the anomalous Hall effect is used to realize the storage of binary data "0" and "1". Compared with the prior art, the device preparation method of the present invention is simpler, lower in cost, and has a short production cycle.

[0014] 2. The structure proposed by the present invention uses gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG) substrate and magnetic film layer rare earth iron garnet material Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) has good lattice matching, with very small differences in lattice constant and thermal expansion coefficient, and the magnetic thin film materials grown on the substrate have excellent quality and good performance.

[0015] 3. Bi-doped HoIG film has better anisotropy. Doping Au into PtBi improves the spin current conversion efficiency and reduces power consumption.

[0016] 4. The critical reversal current of the magnetic moment of the structure proposed by the present invention is small, and the read current is extremely small, which greatly reduces the power consumption and unit write current density and improves the storage speed. The read current and the write current are very different, and the read current does not affect the change of the material magnetic moment, that is, the change of the Hall voltage, and thus does not affect the storage of data. Therefore, the storage device structure proposed by the present invention has a high storage accuracy.

[0017] 5. The high-performance quantum memory device structure proposed by the present invention does not change the Hall voltage when the power is off, and the stored data remains unchanged, which is non-volatile. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a cross-sectional view of the structure of the high-performance quantum memory device of the present invention.

[0019] Figure 2 It is a side view of the structure of the high-performance quantum storage device of the present invention.

[0020] Figure 3 It is a schematic diagram of the data reading and writing function of the memory device of the present invention through the SOT (spin-orbit moment) effect.

[0021] Figure 4 This is a diagram of the Hall resistance test results of the abnormal Hall effect of the memory device of the present invention.

[0022] Figure 5 It is a symbol diagram of the storage device of the present invention in the simulation software.

[0023] Figure 6 It is a process flow chart of manufacturing the high-performance quantum memory device of the present invention. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.

[0025] like Figure 1 As shown, a high-performance quantum memory device structure includes a three-layer material structure. 101 is <111> Single crystal substrate of gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG). 102 is Bi-doped rare earth iron garnet Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) film, with a thickness of 30-150nm. 103 is a heavy metal film Au doped PtBi alloy Au:PtBi, with a thickness of 10-15nm. A high-performance quantum memory device structure, the preparation method thereof is as follows Figure 6 As shown in the flow chart, the following steps are included:

[0026] Step 1: First, place a single crystal substrate of gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG) substrate cleaning, comprising the following steps:

[0027] Step 1.1. Gd-Ga-Garnet 3 Ga 5 O 12 , GGG) substrate was placed in anhydrous ethanol for ultrasonic treatment;

[0028] Step 1.2. Place the substrate processed in step 1.1 in a polishing furnace and preheat at 300°C;

[0029] Step 1.3. Put the substrate treated in step 1.2 into hot acid solution for polishing;

[0030] Step 1.4. Transfer the substrate treated in step 1.3 to a sodium hydroxide solution at 200-250°C and soak it therein, and then soak and clean it in deionized water at 80-100°C.

[0031] Step 1.5. Transfer the substrate treated in step 1.4 to anhydrous ethanol and ultrasonicate for 10 to 15 minutes, then dry it in a vacuum oven.

[0032] Step 2: <111> Single crystal substrate of gadolinium gallium garnet (Gd 3 Ga 5 O 12 , GGG) substrate using liquid phase epitaxy to grow the second layer of Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) film with a thickness of 30-150 nm. The process comprises the following steps:

[0033] Step 2.1. Select the raw material Ga for growing thin films 2 O 3 、Ho 2 O 3 , Fe 2 O 3 、Bi 2 O 3 , according to the proportion Ga 2 O 3 :Fe 2 O 3 =0.10~0.135,Ho 2 O 3 :Fe 2 O 3 =0.1~0.2,Bi 2 O 3 :Fe2O3=5~11; The raw materials are mixed evenly and melted in a crucible at 1000℃ for 24 hours, and then cooled to the growth temperature to obtain a melt;

[0034] Step 2.2. Fix the substrate on the substrate holder so that its surface forms an angle of 10° with the melt surface, then place the substrate holder into the melt, adjust the substrate rotation speed to 75 rpm / min, and the growth temperature to about 885°C;

[0035] Step 2.3. Change the rotation direction of the substrate every five seconds for a total of 60 seconds. Then take out the GGG substrate and let it stand for 20 minutes, then take it out from the furnace body and let it stand again;

[0036] Step 2.4. Place the substrate obtained in step 2.3 in hot nitric acid to remove the flux remaining on the substrate surface and obtain 30-150nm Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 )film.

[0037] Step 3: In Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) film by direct current magnetron sputtering to prepare Au:PtBi film with a thickness of 10-15nm. The method comprises the following steps:

[0038] Step 3.1. Grow Bi:HoIG (Bi x Ho 3-x Fe 5 O 12 ) The film substrate is cleaned with anhydrous ethanol and deionized water, blown dry with a nitrogen gun and placed in a magnetron sputtering device;

[0039] Step 3.2. Adjust the back vacuum of the main chamber to 7×10 -5 Pa, introduce Ar gas to stabilize the pressure of the main vacuum chamber at 0.3Pa;

[0040] Step 3.3. Set the DC sputtering power to 10 W and open the baffle of the heavy metal target. After sputtering for one minute, close the baffle, turn off the argon valve and the DC sputtering source, and you can get an Au:PtBi film with a thickness of 10 nm.

[0041] Step 4: Use photolithography to carve a cross-shaped pattern on the surface of the heavy metal film. The cross-shaped pattern to be retained is determined by applying photoresist on the surface of the heavy metal film, and then undergoes pre-baking, exposure, development, hardening and other process flows, and finally uses ion beam etching to remove the photoresist to obtain the final pattern.

[0042] Example 1

[0043] Storage mechanism of a high-performance quantum memory device structure, change of Hall voltage:

[0044] like Figure 2 As shown, when an in-plane current is passed around the device, and the current density is greater than the critical reversal current density of the material magnetic moment, the material magnetic moment is induced to flip through the SOT (spin-orbit moment) effect, and the direction of the magnetic moment is vertically upward 205, and the memory device is set to logic "1". When the in-plane current is reversed, the direction of the magnetic moment is vertically downward, and the memory device is set to logic "0". A very small detection current is passed in the direction of 202, and the Hall voltage can be obtained at ports 203 and 204, thereby obtaining the Hall resistance.

[0045] According to the method shown above, the change of Hall resistance is tested and the following is obtained: Figure 4 From the Hall resistance test result diagram of the anomalous Hall effect shown in the figure, it can be seen that the high and low resistance values ​​of the Hall resistance are around ±0.6mΩ.

[0046] Example 2

[0047] A high-performance quantum memory device structure uses the SOT (spin-orbit moment) effect to achieve read and write functions:

[0048] like Figure 3 As shown, 302, 303, and 304 constitute the high-performance quantum memory device of the present invention. 301 is the current line for reading data, which is used to read the Hall voltage of the memory device. If it is positive, it is in the "1" state, and if it is negative, it is in the "0" state. 305 is the in-plane current for writing data, which acts on the spin heterojunction to induce magnetic moment reversal and store binary numbers "1" and "0". 306 is a MOS tube used as a switch to control the data storage process.

[0049] A high-performance quantum memory device structure uses SOT (spin-orbit moment) to achieve read and write functions in the following process:

[0050] Writing process: When receiving the data storage signal, the gate voltage of 306 MOS tube increases, making the MOS tube conductive, generating a writing current greater than the critical inversion current density in the current plane of writing data, and flipping the internal magnetic moment of the device through the SOT (spin-orbit moment) effect to realize the data storage process.

[0051] Reading process: When a data reading signal is received, a reading current is generated in the reading current path 301, and the current flows through the cross-shaped heavy metal film, and a Hall voltage is detected between 203 and 204, thereby realizing the data reading process.

[0052] Example 3

[0053] A high-performance quantum memory device structure can be used in the simulation software Cadence Virtuoso, in which more complex memory circuits can be designed and circuit performance optimized.

[0054] like Figure 5 As shown, the spin heterojunction device is modeled in the simulation software through the Verilog-A code, and is equivalent to a four-port device, where the four ports are Figure 5Ports 501, 502, 503, and 504 in the device. Both the read current and the write current flow through ports 504 and 502, and ports 501 and 503 are used to detect the size of the Hall voltage. When a very small detection current is passed, there is only a very small Hall voltage at ports 501 and 503, so the voltages of these two ports can be amplified by an operational amplifier to make the Hall voltage more intuitive. When writing data, a current greater than the critical flip density is generated by controlling the logic gate to pass through ports 504 and 502 to induce magnetic moment flipping through the SOT effect, thereby realizing the storage of "1" and "0". With the above-mentioned four-port equivalent model, the design of the circuit is simpler and faster, which saves time and cost. The above is a specific implementation of the present invention. Without departing from the principle of the present invention, technicians in this field can also make many variations and improvements, which should also be regarded as the protection scope of the present invention.

Claims

1. A high-performance quantum memory device structure, characterized in that The construction of a spin heterojunction consists of three layers of materials from bottom to top: The first layer is the substrate, which is used to grow thin films and carry logic devices; The second layer is a magnetic material film layer, which is located above the substrate layer; The third layer is a heavy metal layer, which is located above the magnetic film layer. Among them, the substrate is a single crystal substrate, the magnetic film layer uses a nano-scale film, and the heavy metal layer adopts a cross-shaped structure to construct an anisotropic film to achieve the anomalous Hall effect (AHE), realize the change of positive and negative Hall voltage, and then realize the storage of binary data "1" and "0".

2. A high-performance quantum memory device structure according to claim 1, characterized in that: Single crystal substrate <111> Gd3Ga5O 12 , GGG).

3. A high-performance quantum memory device structure according to claim 1, characterized in that: The magnetic film layer is made of Bi-doped rare earth iron garnet Bi:HoIG (Bi x Ho 3-x Fe5O 12 ) thin film, by liquid phase epitaxy <111> Gd3Ga5O 12 , GGG) grown on Bi:HoIG (Bi x Ho 3-x Fe5O 12 ) film, the thickness of the magnetic film layer is 30-150nm.

4. A high-performance quantum memory device structure according to claim 1, characterized in that: The heavy metal film layer is made of Au-doped PtBi alloy Au:PtBi, which is deposited on Bi:HoIG (Bi x Ho 3-x Fe5O 12 ) film, which was photoetched into a cross-shaped structure with a heavy metal layer thickness of 10-15 nm.

5. A high-performance quantum memory device structure according to claim 1, characterized in that: When the Hall voltage is positive, the memory device is set to logic "1", and when the Hall voltage is negative, the memory device is set to logic "0". When writing data, the write current uses the SOT (spin-orbit moment) effect to induce the magnetic moment to flip, thereby realizing the transition from data "0" to "1".

6. A high-performance quantum memory device structure according to claim 1, characterized in that: By passing a very small detection current through the two ends of the cross-shaped structure of the heavy metal layer, the Hall voltage can be detected at the other two ends to realize the reading of data "0" and "1".